Pengaruh Faktor Oseanografi Terhadap Hasil Tangkapan Masyarakat Nelayan Di Kelurahan Namosain Kecamatan Alak Kota Kupang - Dian Kusuma Dewi; Hamza H Wulakada; Arfita Rahmawati (Universitas Negeri Gorontalo, 2025)
Fishing communities are coastal communities that are highly dependent on marine conditions in carrying out fishing activities. The dynamics of oceanographic conditions, such as ocean currents and tidal fluctuations, play an important role in determining fish distribution, fishing safety, and the success of fishing activities. This study aims to examine the effect of oceanographic factors on the catch of fishing communities in Namosain Village, Alak District, Kupang City. This research employed a quantitative approach using a survey method. The research population consisted of fishermen in Namosain Village, with the sample determined using the Slovin formula. The results showed that partially, ocean currents had a significant effect on fishermen’s catch, while tidal fluctuations did not have a significant effect on fishermen’s catch. However, simultaneously, oceanographic factors had a significant effect on the catch of fishing communities in Namosain Village. These findings indicate that oceanographic conditions play an important role in determining the success of fishing activities; therefore, adaptation efforts and increased fishermen’s understanding of marine dynamics are needed to support the sustainability of capture fisheries and improve the welfare of coastal fishing communities.